2000
DOI: 10.1210/endo.141.12.7818
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Hormonal Regulation of Three Secretory Proteins (Prostatic Secretory Protein-PSP94, Probasin, and Seminal Vesicle Secretion II) in Rat Lateral Prostate**This work was supported by an RGC Earmarked Research Grant (CUHK 4131/00M) from the Hong Kong Research Grant Council (to F.L.C.) and a grant from the Medical Research Council of Canada (to J.W.X.).

Abstract: The rat dorsolateral prostate secretes several major known proteins, although their physiological and reproductive functions are largely undefined. In the present study we examined and compared the in vivo hormonal regulation of the messenger RNA (mRNA) expression of three major secretory proteins, including prostatic secretory protein of 94 amino acids (PSP94 or beta-microseminoprotein), probasin, and seminal vesicle secretion II (SVSII), in long-term castrated lateral prostates (LP) by in situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Probasin, Nkx3.1, and prostatic secretory protein-94 (PSP94) are three prostate-specific proteins known to be transcriptionally regulated by androgens (16,17). However, it is unknown whether stromal AR or epithelial AR is responsible for their expression.…”
Section: Loss Of Epithelial Ar Decreases Androgen-regulated Gene Exprmentioning
confidence: 99%
“…Probasin, Nkx3.1, and prostatic secretory protein-94 (PSP94) are three prostate-specific proteins known to be transcriptionally regulated by androgens (16,17). However, it is unknown whether stromal AR or epithelial AR is responsible for their expression.…”
Section: Loss Of Epithelial Ar Decreases Androgen-regulated Gene Exprmentioning
confidence: 99%
“…Prostate secretory protein of 94 amino acids (PSP94, gene name MSMB ) is one of the first three secretory proteins in the prostate to be identified, in addition to PSA and PSAP 203 . PSP94 was originally identified as beta-microseminoprotein (MSMB) 204 , or beta-inhibin 205 , and is an androgen-regulated immunoglobulin-binding factor that is secreted into seminal plasma 206209 . Its specific function is still uncertain, but it has been suggested that it increases sperm quality 210 and acts as a fungicidal agent in sperm 211 .…”
Section: Prostate Specific Markersmentioning
confidence: 99%